Ethnobotanical survey of medicinal flora in the rural community Rio dos Couros, state of Mato Grosso, Brazil - Costa, Ineilian B. C. da [UNESP]; Bonfim, Filipe P. G. [UNESP]; Pasa, Maria C.; Montero, Daniel A. V. [UNESP] (Univ Santiago Chile Casa, 2017)
The aim of this work was to register the traditional knowledge about medicinal plants, as well as raise the socioeconomic profile of the residents from the community Rio dos Couros (Brazil), in order to relate them the level of botanical knowledge. The methodology adopted was the snowball, through semi-structured interviews. Levels of agreement regarding the main uses (PUC) and use value (UV) were applied, as well as the ICD for classification of health problems. Difference of age, residence time and individual income were elements that interfered in the level of botanical knowledge. We recorded 81 different plants distributed in 38 botanical families, with Fabaceae as the most cited. The highest value for PUCc was attributed to Strychnos pseudoquina (87%), and the respiratory problem was one of the most common diseases among the community.
Keywords: Ethnobotany; Medicinal plants; Biodiversity; Traditional knowledge